PENINGKATAN LITERASI KEUANGAN KRAMA ISTRI MELALUI PELATIHAN DAN PENDAMPINGAN PEMBUKUAN SEDERHANA - Yogantara, Komang Krishna; Prayogi, Putu Agus (Synergy and Society Service, 2024)
Krama Istri, the term for mothers in a village in Bali, is expected to be the vanguard to strengthen the pillars of the village economy in achieving sustainable development goals or Sustainable Development Goals (SDGs). Therefore, krama istri must have good financial management so that the family economy can be run sustainably. One of them is by having correct financial records and what is needed to make decisions in planning the next family economic strategy. Krama istri who are members of the Family Empowerment and Welfare (PKK) in Cepaka Village, Tabanan-Bali do not yet have good records. The results of the training and mentoring made this simple bookkeeping increase the krama istri's awareness of the importance of the information produced as a basis for decision making and strategy development to achieve a sustainable family economy.